2023
DOI: 10.1021/acsnano.2c12676
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Patterning of Binary Ligand Mixtures on CdSe Nanocrystals: From Random to Janus Packing

Abstract: Binary compositions of surface ligands are known to improve the colloidal stability and fluorescence quantum yield of nanocrystals (NCs), due to ligand−ligand interactions and surface organization. Herein, we follow the thermodynamics of a ligand exchange reaction of CdSe NCs with alkylthiol mixtures. The effects of ligand polarity and length difference on ligand packing were investigated using isothermal titration calorimetry (ITC). The thermodynamic signature of the formation of mixed ligand shells was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…However, these indirect methods for studying thermodynamics have their limitations. With the well-known surface of QDs and the establishment of ligand exchange models, ITC, a direct method for monitoring thermal change, is increasingly used to study the thermodynamics of ligand exchange. , Thus, a more in-depth characterization of the ligand exchange can be conducted to reflect the most authentic ligand exchange. In addition to the coordination between the head groups of organic ligands and the surface of QDs, there is a weak noncovalent interaction between the tail groups of ligands.…”
Section: Thermodynamics Of Ligand Exchangementioning
confidence: 99%
“…However, these indirect methods for studying thermodynamics have their limitations. With the well-known surface of QDs and the establishment of ligand exchange models, ITC, a direct method for monitoring thermal change, is increasingly used to study the thermodynamics of ligand exchange. , Thus, a more in-depth characterization of the ligand exchange can be conducted to reflect the most authentic ligand exchange. In addition to the coordination between the head groups of organic ligands and the surface of QDs, there is a weak noncovalent interaction between the tail groups of ligands.…”
Section: Thermodynamics Of Ligand Exchangementioning
confidence: 99%
“…Indeed, QDs are an important research area in nanoscience and nanotechnology and while the research in the field is constantly moving forward, there are a number of challenges . For example, detailed characterization of the ligand shell composition is required to optimize NC properties and surface interactions for a vast array of applications. Transferring chirality from enantiomeric molecules to colloidal QDs represents another level of tailorability and has attracted immense attention across chemistry, materials, and biomedical science. , Chiroptical properties of NCs arouse interest at the level of basic research, , as well as in the context of various applications, including photonics, catalysis, sensing, and biomedicine. For instance, nanomaterials fabricated using chiral ligands have aroused substantial interest due to the special chirality-dependent biological effects, and a recent seminal study demonstrated that nanoscale chirality can be exploited to modulate immunological responses and various types of chiral nanoparticles have been explored in cancer therapy . Hence, the development of chiroptically active colloidal QDs and understanding of their optical activity have been a vital issue of nanoresearch over the past decade , following the first observation of chiroptical activity in CdS QDs prepared by microwave-assisted synthesis in the presence of l - or d -penicillamine by Moloney et al in 2007 .…”
Section: Introductionmentioning
confidence: 99%
“…This area of research has been dominated by heavy metal-based QDs. Commonly used protocol for the preparation of metal-based QDs involves postsynthetic ligand replacement by chiral molecules after the achiral pristine particle synthesis has been completed. Nevertheless, while adjusting the chirality of NCs, this approach involving ligand exchange reactions has many disadvantages and, for example, may induce uncontrollable changes to the NC surface upon ligand exchange and ultimately, in many cases, lead to the formation of mixed ligand shells. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…isotherm methods, such as the Langmuir isotherm, fail to capture the effects of composition dependent inter-ligand interactions on the surfaces of nanocrystals. 8,55,57,58,64,66,67,73,74 As a result, analyses of isothermal titration calorimetry or 1 H NMR measurements alone may lead to inaccurate results. 7 When considering ligand exchange reactions on the surfaces of colloidal nanocrystals, several factors can influence how a reaction occurs.…”
mentioning
confidence: 99%